Analisis Peran Industri Agro Terhadap Pembangunan Ekonomi Kalimantan Tengah - Raharjo, Hafid; Nunung Kusnadi; Widyastutik (STEKOM PRESS, 2023)
Central Kalimantan Province has potential in the agricultural sector. The contribution of the agricultural sector, particularly from plantations, makes a significant contribution to the economy of the Central Kalimantan region. Despite having an abundant supply of raw materials, the processing industry's ability to increase the added value of agricultural and plantation commodities is still not optimal due to limited processing facilities. Therefore, to accurately determine the contribution of the industrial sector, especially the agro industry to the regional economy in Central Kalimantan, an analysis can be carried out using the 2016 input-output table. The results of the study show that two sub-sectors of the agro industry, namely the food and beverage the chemical, pharmaceutical and traditional medicine industries are the leading industrial sectors in Central Kalimantan. This explains that the agro-industrial sector can become a leading sector because it is able to improve the regional economy and develop other sectors.